Modifikasi Pattern Informatics untuk Prediksi Hotspot Aktivitas Seismik pada Gempa di Pulau Jawa - Adi Wibowo; Asep Insani; Boko Nurdiyanto S. (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Earthquake is a serious problem in economic, social, and cultural point of view. The forecasting and prediction can be one way solution in reducing the effects of earthquakes in a region. In this paper, pattern informatics method was modified with time parameters to conduct hotspot prediction of seismic activity for the earthquake forecasting in Java. The experiment using seismic activity and earthquake data in Java were conducted to examine the perfomance of proposed method with several period prediction scenarios. The prediction results show an improvement of prediction result and shorten the prediction period.